A Note on Perturbation Estimations for Spectral Projectors. (25th October 2020) - Song, Chuanning; Wei, Yimin; Xu, Qingxiang
Abstract: For any singular matrix A ∈ C n × n, let A D, A π = I n − A A D be its Drazin inverse and spectral projector, respectively. Let | | · | | be any norm on C n × n and A ¯ ∈ C n × n be any stable perturbation of A . In this note a sufficient condition is given under which | | A ¯ π − A π | | < 1 .